Unbroken - Jolie, Angelina; O'Connel, Jack; Gleeson, Domhnall; Hedlund, Garrett; Jolie Pas; Universal Pictures (California : Universal Studios, 2014)
As a boy, Louis is always in trouble but with the help of his older brother he channels his energy into running and becomes a 1936 Olympic competitor. When World War II breaks out, Louis enlists in the military. After a near-fatal plane crash in WWII, he spends a harrowing 47 days in a raft with two fellow crewmen before he's caught by the Japanese navy and sent to a prisoner-of-war camp. Here he becomes the favourite target of a particularly brutal prison guard because of his Olympic history.
Based on the book by Laura Hillenbrand.
Executive producer, Mick Garris, Thomas Tull & Jon Jashni ; music, Alexandre Desplat ; editors, Tim Squyers, William Goldenberg ; director of photography, Roger Deakins.
Jack O'Connel, Domhnall Gleeson, Miyavi, Garrett Hedlund, Finn Wittrock.
LPF: P13
DVD format, Letterbox (2.40:1), Region 3, Dolby Digital.
In English with optional Bahasa Indonesia, Brazilian Portuguese, Cantonese, Korean, Latin American Spanish, Thai & Traditional Chinese.
Keywords: Zamperini, Louis, -- 1917-2014 -- Drama; World War, 1939-1945 -- Prisoners and prisons, Japanese -- Drama; Olympic athletes -- Drama; Biographical films